1996
DOI: 10.1107/s0909049595013574
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Accurate Intensity Calibration of Area X-ray Detectors at Almost Arbitrary Energy

Abstract: A novel intensity uniformity calibration method for area X-ray detectors is described. In diffraction experiments, amorphous lithium glass plates, containing doping elements chosen for their K edges just below the energy of the main beam, replace the crystallographic samples for the calibration measurement. The fluorescent emission excited by the X-ray beam is almost isotropic. It has exactly the same geometry as the diffracted radiation, and can be obtained at the same wavelength by proper selection of the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…Cocrystals: Initial data were collected from a single cocrystal flash frozen using an Oxford Cryosystems Cryostream on beam line BL19 (Thompson et al, 1996) at the ESRF, Grenoble. Crystals were soaked in a cryoprotectant solution containing 15% MPD (v/v) 30% PEG4000 (w/v), 0.1 M sodium citrate, pH 5.6, 0.2 M ammonium acetate, 25 mM 2,3 sialyllactose prior to freezing in the dry air stream at 104 K; 0,979-A wavelength synchrotron radiation was used and data recorded using a CCD-based detector (Moy, 1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cocrystals: Initial data were collected from a single cocrystal flash frozen using an Oxford Cryosystems Cryostream on beam line BL19 (Thompson et al, 1996) at the ESRF, Grenoble. Crystals were soaked in a cryoprotectant solution containing 15% MPD (v/v) 30% PEG4000 (w/v), 0.1 M sodium citrate, pH 5.6, 0.2 M ammonium acetate, 25 mM 2,3 sialyllactose prior to freezing in the dry air stream at 104 K; 0,979-A wavelength synchrotron radiation was used and data recorded using a CCD-based detector (Moy, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Crystals were soaked in a cryoprotectant solution containing 15% MPD (v/v) 30% PEG4000 (w/v), 0.1 M sodium citrate, pH 5.6, 0.2 M ammonium acetate, 25 mM 2,3 sialyllactose prior to freezing in the dry air stream at 104 K; 0,979-A wavelength synchrotron radiation was used and data recorded using a CCD-based detector (Moy, 1994). X-ray data were collected by the oscillation method using 1" oscillations, calibrated, and corrected for spatial distortion (Hammersley et al, 1995;Moy et al, 1996). High-resolution data to a maximum resolution of 1.85 A were collected using 1 .O-A wavelength synchrotron radiation (0.1 -mm collimation) at 14 "C on beam line BL6A2 (Sakabe, 1991) of the Photon Factory, Tskuba, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…It is based upon a method recently developed for calibrating area X-ray detectors (Moy et al, 1996). A glass containing selected elements is held in a polychromatic beam of X-rays and the¯uorescence lines from the selected elements are used for the energy calibration.…”
Section: Methodsmentioning
confidence: 99%
“…We do not know of a perfect isotropic point source at arbitrary X-ray energies. However, we have found that very smooth 'floodfield'-~ emission may be obtained at a wide variety of X-ray energies by using the fluorescence from doped dilithium tetraborate glasses (Moy et al, 1996). These glasses are relatively easy to manufacture from raw materials provided that a few basic preparation rules are followed (Foust, 1995).…”
Section: Non-uniformity Of Response Correctionmentioning
confidence: 99%